Effects of an electronic health record‐based mobility assessment and automated referral for inpatient physical therapy on patient outcomes: A quasi‐experimental study. (20th November 2022) - Chou, Aileen; Johnson, Joshua K.; Jones, Daniel B.; Euloth, Tracey; Matcho, Beth A.; Bilderback, Andrew; Freburger, Janet K.
Abstract: Objective: To assess the effectiveness of a hospital physical therapy (PT) referral triggered by scores on a mobility assessment embedded in the electronic health record (EHR) and completed by nursing staff on hospital admission. Data Sources: EHR and billing data from 12 acute care hospitals in a western Pennsylvania health system (January 2017–February 2018) and 11 acute care hospitals in a northeastern Ohio health system (August 2019–July 2021). Study Design: We utilized a regression discontinuity design to compare patients admitted to PA hospitals with stroke who reached the mobility score threshold for an EHR‐PT referral (treatment) to those who did not (control). Outcomes were hospital length of stay (LOS) and 30‐day readmission or mortality. Control variables included demographics, insurance, income, and comorbidities. Hospital systems with EHR‐PT referrals were also compared to those without (OH hospitals as alternative control). Subgroup analyses based on age were also conducted. Data Extraction: We identified adult patients with a primary or secondary diagnosis of stroke and mobility assessments completed by nursing ( n = 4859 in PA hospitals, n = 1749 in OH hospitals) who completed their inpatient stay. Principal Findings: In the PA hospitals, patients with EHR‐PT referrals had an 11.4 percentage‐point decrease in their 30‐day readmission or mortality rates (95% CI −0.57, −0.01) relative to the control. This effect was not observed in the OH hospitals for 30‐day readmission ( β = 0.01; 95% CI −0.25, 0.26). Adults over 60 years old with EHR‐PT referrals in PA had a 26.2 percentage‐point (95% CI −0.88, −0.19) decreased risk of readmission or mortality compared to those without. Unclear relationships exist between EHR‐PT referrals and hospital LOS in PA. Conclusions: Health systems should consider methodologies to facilitate early acute care hospital PT referrals informed by mobility assessments.